Targeted mitochondrial therapy using MitoQ shows equivalent renoprotection to angiotensin converting enzyme inhibition but no combined synergy in diabetes. Issue 1 (December 2017) - Ward, Micheal; Flemming, Nicole; Gallo, Linda; Fotheringham, Amelia; McCarthy, Domenica; Zhuang, Aowen; Tang, Peter; Borg, Danielle; Shaw, Hannah; Harvie, Benjamin; Briskey, David; Roberts, Llion; et al.
Abstract Mitochondrial dysfunction is a pathological mediator of diabetic kidney disease (DKD). Our objective was to test the mitochondrially targeted agent, MitoQ, alone and in combination with first line therapy for DKD. Intervention therapies (i) vehicle (D); (ii) MitoQ (DMitoQ;0.6 mg/kg/day); (iii) Ramipril (DRam;3 mg/kg/day) or (iv) combination (DCoAd) were administered to male diabeticdb /db mice for 12 weeks (n = 11–13/group). Non-diabetic (C)db /m mice were followed concurrently. No therapy altered glycaemic control or body weight. By the study end, both monotherapies improved renal function, decreasing glomerular hyperfiltration and albuminuria. All therapies prevented tubulointerstitial collagen deposition, but glomerular mesangial expansion was unaffected. Renal cortical concentrations of ATP, ADP, AMP, cAMP, creatinine phosphate and ATP:AMP ratio were increased by diabetes and mostly decreased with therapy. A higher creatine phosphate:ATP ratio in diabetic kidney cortices, suggested a decrease in ATP consumption. Diabetes elevated glucose 6-phosphate, fructose 6-phosphate and oxidised (NAD+ and NADP+) and reduced (NADH) nicotinamide dinucleotides, which therapy decreased generally. Diabetes increased mitochondrial oxygen consumption (OCR) at complex II-IV. MitoQ further increased OCR but decreased ATP, suggesting mitochondrial uncoupling as its mechanism of action. MitoQ showed renoprotection equivalent to ramipril but no synergistic benefits of combining these agents were shown.